2022
DOI: 10.1097/yic.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality traits in following quarantine orders during the COVID-19 pandemic

Abstract: Patients’ personalities seem to affect their response to the COVID-19 pandemic. This study examined the association of personality traits and characteristics of Iranian COVID-19 outpatients with their compliance to nonmandatory quarantine orders. This cross-sectional study was conducted in 2020-2021 on 97 COVID-19 outpatients. The temperament and character inventory-revised short version (TCI-RS) and a self-report checklist assessing compliance with quarantine orders were used to collect data. SPSS was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Five studies reported following official guidance in the country where the study was conducted, but did not specify what the guidance was. [21, 36, 37, 39] One study defined self-isolation as following “isolation measures (e.g., avoiding contact with others, hygiene measures, wearing a mask)”. [30] Twelve studies reported “self-isolate” or “quarantine” (or some such variant), but did not define required behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies reported following official guidance in the country where the study was conducted, but did not specify what the guidance was. [21, 36, 37, 39] One study defined self-isolation as following “isolation measures (e.g., avoiding contact with others, hygiene measures, wearing a mask)”. [30] Twelve studies reported “self-isolate” or “quarantine” (or some such variant), but did not define required behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…[23, 29, 30, 34–43, 45–68, 73, 75–78, 8183] Of these, 24 were assessed using the ROBINS-E. Analyses of associations from seven studies were at very high risk of bias, [30, 34, 37, 38, 73, 77, 78, 83], 15 were at high risk of bias, [23, 29, 35, 36, 40–43, 47–68, 75, 76, 81, 82] and two had some concerns (Supplement S6). [39, 45] One study was assessed using the ROBINS-I and was rated as very high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations